The impact of social face consciousness on taking-charge behavior of employees: The mediating effect of thriving at work, and the moderating effect of ethical leadership and general self-efficacy - Li, Yuqi; Wang, Jia-Fure (Edelweiss Applied Science and Technology, 2025)
Under the dual impacts of digital transformation and the post-pandemic era, organizational sustainability increasingly relies on employees’ proactive taking charge behavior. Against this backdrop, this study constructs a moderated mediation model based on proactive motivation theory within Chinese organizational contexts, aiming to uncover the influence mechanism of social face consciousness on employee taking charge behavior and its boundary conditions. Through purposive sampling of employees from multiple enterprises and institutions, 631 valid questionnaires were collected. Data were analyzed using structural equation modeling (SEM) and hierarchical regression analysis. The findings reveal that both face-gaining consciousness and face-losing consciousness positively influence thriving at work. Thriving at work significantly enhances taking charge behavior; face-gaining consciousness and face-losing consciousness directly and positively affect taking charge behavior; thriving at work mediates the positive relationships between face-gaining/face-losing consciousness and taking charge behavior; general self-efficacy positively moderates the effect of thriving at work on taking charge behavior.